Comorbidities Associated with Obstructive Sleep Apnea: a Retrospective Study - Pinto,José Antonio (2016)
Abstract Introduction Obstructive sleep apnea (OSA) is characterized by partial or complete recurrent upper airway obstruction during sleep. OSA brings many adverse consequences, such as hypertension, obesity, diabetes mellitus, cardiac and encephalic alterations, behavioral, among others, resulting in a significant source of public health care by generating a high financial and social impact. The importance of this assessment proves to be useful, because the incidence of patients with comorbidities associated with AOS has been increasing consistently and presents significant influence in natural disease history. Objective The objective of this study is to assess major comorbidities associated with obstructive sleep apnea (OSA) and prevalence in a group of patients diagnosed clinically and polysomnographically with OSA. Methods This is a retrospective study of 100 charts from patients previously diagnosed with OSA in our service between October 2010 and January 2013. Results We evaluated 100 patients with OSA (84 men and 16 women) with a mean age of 50.05 years (range 19-75 years). The prevalence of comorbidities were hypertension (39%), obesity (34%), depression (19%), gastroesophageal reflux disease (GERD) (18%), diabetes mellitus (15%), hypercholesterolemia (10%), asthma (4%), and no comorbidities (33%). Comorbidities occurred in 56.2% patients diagnosed with mild OSA, 67.6% with moderate OSA, and 70% of patients with severe OSA. Conclusion According to the current literature data and the values obtained in our paper, we can correlate through expressive values obesity with OSA and their apnea hypopnea index (AHI) values. However, despite significant prevalence of OSA with other comorbidities, our study could not render expressive significance values able to justify their correlations.